Identification of the CNGC Gene Family in Rice and Mining of Alleles for Application in Rice Improvement - Xinchen Wang; Fengcai Wu; Jinguo Zhang; Yaling Bao; Nansheng Wang; Guohui Dou; Dezhuang Meng; Xingmeng Wang; Jianfeng Li; Yingyao Shi (Plants, 2023)
Cyclic nucleotide-gated ion channel (CNGC) gene regulation plays important roles in plant immune and abiotic stress response. Here, we identified 16 CNGC genes in rice (Oryza sativa). Then, we analyzed their chromosomal location, physicochemical properties, subcellular localization, gene functional interaction network, cis-acting elements, phylogenetic relationships, collinearity, expression in tissues under normal conditions and abiotic stresses, and geng-cds-haplotype (gcHap) diversity in 3010 gcHaps. As a result, OsCNGC3 (Os06g0527300) was identified as a gene different from previous report, and OsCNGC genes were found to play important roles in rice population differentiation and rice improvement. Our results revealed their very strong differentiation between subspecies and populations, important roles in response to abiotic stresses, as well as strong genetic bottleneck effects and artificial selection of gcHap diversity in the modern breeding process of Xian (indica) and Geng (japonica) populations. The results also suggested that natural variations in most rice CNGC loci are potentially valuable for improving rice productivity and tolerance to abiotic stresses. The favorable alleles at the CNGC loci should be explored to facilitate their application in future rice improvement.